Aneurysm of the cranial mesenteric artery as a site of carriage of Salmonella enterica subsp. enterica serovar Abortusequi in the horse. (July 2016) - Niwa, Hidekazu; Hobo, Seiji; Kinoshita, Yuta; Muranaka, Masanori; Ochi, Akihiro; Ueno, Takanori; Oku, Kazuomi; Hariu, Kazuhisa; Katayama, Yoshinari
Salmonella enterica subsp. enterica serovar Abortusequi is a pathogen restricted to horses. Our investigation targeted 4 draft horses (9–10 months old) kept on a Japanese farm that had suffered an outbreak of S. Abortusequi abortion. The 4 horses were suspected to be carriers of the bacterium owing to their high agglutination titers (≥1:2, 560) in tube agglutination testing. The owners' on-farm observations confirmed that the horses had no apparent abnormalities, and S. Abortusequi was not isolated from their blood, rectal swabs, or sternal bone marrow fluid at antemortem investigation. However, at autopsy, all horses displayed the following: suppurative aneurysm of the cranial mesenteric artery with heavy infection with Strongylus vulgaris larvae; heavy intestinal parasitic infection with Gasterophilus intestinalis, Parascaris equorum, Anoplocephala perfoliata, and S. vulgaris ; and enlargement of the systemic lymph nodes. In each case, large numbers of S. Abortusequi were isolated from the anterior mesenteric artery thrombus. The thrombus isolates harbored a single virulence plasmid, and the pulsed-field gel electrophoresis profiles of the isolates were identical not only to each other but also to those of Japanese enzootic strains of S. Abortusequi. These results reveal that parasitic aneurysms of the cranial mesenteric artery should be considered an important possible site of carriage of S. Abortusequi in horses. The results also suggest high clonality of the isolated serovar in the horse population in Japan.